A novel variant of COL6A3 c.6817-2(IVS27)A>G causing Bethlem myopathy: A case report - Li, Maohua; Huang, Jiandi; Liu, Min; Duan, Chunmei; Guo, Hong; Chen, Xiaoyan; Wang, Yue (Frontiers in Neurology, 2023)
Bethlem myopathy(BM) is caused by mutations in one of the collagen VI genes. It is a mildly progressive disorder, characterised by proximal muscle weakness and joint contractures mainly involving the elbows, ankles, and fingers.BM is almost exclusively caused by dominant COL6A1, COL6A2, or COL6A3 mutations.However, few cases of collagen VI mutations with bilateral facial weakness and Beevor’s sign has been reported.We present a female patient of 50 years old, with symptoms of muscle weakness beginning in childhood and of very slowly progression. At the age of 50, the neurological examination revealed bilateral facial weakness and asymmetrical proximal muscle weakness,and positive Beevor’s sign. Serum creatine kinase values were slightly elevated, electromyographic study revealed myopathic changes and muscle MRI of the lower limbs showed the typical muscle MRI associated with COL6 related myopathy. Whole genome sequencing technology identified the heterozygous mutation c.6817-2(IVS27)A>G in COL6A3 gene, which was a novel mutation.We report a further case of BM, which is caused by recessive COL6A3 intron variation,widen the clinical spectrum and genetic heterogeneity of Bethlem myopathy.